Correlation analysis of Hashimoto’s thyroiditis with papillary thyroid carcinoma occurrence and its central lymph node metastasis: a single center experience - Sun, Kang; Wang, Xiaoming; Chen, Dexuan; Ma, Chaoqun (Frontiers in Endocrinology, 2025)
PurposeThis study investigates the clinicopathological characteristics of papillary thyroid carcinoma (PTC) with coexisting Hashimoto’s thyroiditis (HT) and further explores the risk factors for central lymph node metastasis (CLNM) in PTC.MethodA retrospective analysis was conducted on 415 PTC patients who underwent surgical treatment for thyroid cancer at the First Affiliated Hospital of Anhui University of Chinese Medicine from 2016 to 2022. Clinicopathological features were compared between PTC patients with and without HT. Univariate and multivariate logistic regression were used to analyze the risk factors of CLNM.ResultThe PTC+HT group had a higher proportion of female patients (85.5%) than the PTC group (P<0.05). Univariate analysis revealed no statistically significant difference between the two groups in eight aspects (all P>0.05). Multivariate analysis showed that HT was positively associated with the total number of central lymph node (CLN) dissected, Thyroid-stimulating hormone (TSH), Thyroid peroxidase antibody (TPOAb), and Thyroglobulin antibodies (TgAb), while identified as a protective factor against invasion with an odds ratio of 0.422 (95%CI 0.209-0.853, P=0.016). Through univariate and multivariate logistic regression, we proved that tumor position, Capsule + Extrathyroidal extension (ETE), multifocal tumors, and the total number of CLN dissected were independent risk factors for CLNM. Multiple linear regression analysis told us that invasion (β= 0.093, p=0.048) had a positively predictive impact on CLN positive rate.ConclusionFemale PTC patients are more prone to concurrent HT, which elevates the levels of TSH, TPOAb, and TgAb. HT not only promotes the longitudinal growth of nodules and PTC development, but also reduces the risk of invasion and CLNM. Therefore, we posit that the impact of HT on PTC patients is a “double-edged sword”. Isthmus, Capsule + ETE, multifocality, age < 55 years old, and male are high-risk factors for CLNM in PTC, while HT is regarded as a protective factor. Capsule + ETE is the primary risk factor affecting the CLN positive rate.